2022
DOI: 10.1161/jaha.122.026378
|View full text |Cite|
|
Sign up to set email alerts
|

Endothelial Foxp1 Regulates Neointimal Hyperplasia Via Matrix Metalloproteinase‐9/Cyclin Dependent Kinase Inhibitor 1B Signal Pathway

Abstract: Background The endothelium is essential for maintaining vascular physiological homeostasis and the endothelial injury leads to the neointimal hyperplasia because of the excessive proliferation of vascular smooth muscle cells. Endothelial Foxp1 (forkhead box P1) has been shown to control endothelial cell (EC) proliferation and migration in vitro. However, whether EC‐Foxp1 participates in neointimal formation in vivo is not clear. Our study aimed to investigate the roles and mechanisms of EC‐Foxp1 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The mechanisms of FOXP1-mediated regulation of tumor growth are multilayered and multidirectional, including those associated with tumor immunity [35], some lncRNAs [36], and cancer-related signal pathways [37]. For example, it has been observed that FOXP1 inhibits the expression of the interleukin-7 (IL-7) receptor α chain (IL-7Rα) in CD8 + T cells and phosphorylates MEK and ERK to exert an anti-tumor effect [38].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of FOXP1-mediated regulation of tumor growth are multilayered and multidirectional, including those associated with tumor immunity [35], some lncRNAs [36], and cancer-related signal pathways [37]. For example, it has been observed that FOXP1 inhibits the expression of the interleukin-7 (IL-7) receptor α chain (IL-7Rα) in CD8 + T cells and phosphorylates MEK and ERK to exert an anti-tumor effect [38].…”
Section: Discussionmentioning
confidence: 99%
“…This factor can directly activate MMP-2 in SMCs and promote their proliferation and migration [ 23 ]. In addition, IL-1β was reported to interact with MMP-9 to delay reendothelialization and promote neointima formation [ 7 , 24 ]. In this study, we showed that a large amount of IL-1β was produced by SMCs after hypoxia-reoxygenation, and reducing IL-1β expression with an siRNA inhibited the proliferation and migration of SMCs.…”
Section: Discussionmentioning
confidence: 99%
“…High neointima AOIs also increased GRNs involved in cell proliferation (JUN), EndoMT (NR2F2, HEY2, and FOXP1), angiogenesis (RUNX1) and fibrosis (ATF3 and ATF4) 27,32,[41][42][43][44][45][46] . Notably, DEGs (CSRP1 and TAGLN) and GRNs (NR2F2, ATF3, FOXP1) encompassed genes which promote EndoMT by regulating or being induced by TGF-β 27,28,32,43 .…”
Section: Activation Signaling and Aggregation' (Me50) Dsa Crosslinkin...mentioning
confidence: 99%
“…Notably, transcripts involved in inhibiting tumor cell proliferation, EMT/fibrosis (OGN) and anti-inflammatory regulators (ZFP36) were also identified in vessels with moderate (2+) and very significant neointima (4+), respectively 39,40 . Major GRNs associated with increasing neointima also included transcription factors involved promoting cell proliferation, migration, EMT/EndoMT, fibrosis (NF2F2, JUN, HEY, ATF3, ATF4, and FOXP1) and angiogenesis (RUNX1) 32,[41][42][43][44][45][46] (Figure 4C).…”
Section: Cav Lesion Progression Is Associated With Distinct Gene Expr...mentioning
confidence: 99%